Layered double hydroxide bio-composites toward excellent systematic anticancer therapy. Issue 17 (13th April 2017) - Mei, Xuan; Liang, Ruizheng; Peng, Liuqi; Hu, Tongyang; Wei, Min
Abstract : A supramolecular bio-composite with an excellent chemotherapy–PDT synergistic anticancer effect is fabricated and shows potential application in the field of cancer therapy. Abstract : Multi-therapeutic methodologies have attracted considerable attention toward cancer therapy, which can overcome the limitation of a single therapy and achieve an optimized anticancer efficacy. Herein, we prepared a systematic anticancer drug by intercalating zinc phthalocyanines (ZnPc) into a layered double hydroxide (LDH) gallery, followed by loading doxorubicin (DOX) on the surface (denoted as ZnPc-DOX/LDH). ZnPc is accommodated in the interlayer region of the LDH, which results in a largely enhanced photodynamic therapeutic (PDT) efficiency; while the physisorbed DOX affords a chemotherapeutic effect. In vitro tests performed with KB cells indicate a synergistic anticancer performance as well as excellent biocompatibility compared with pristine ZnPc and DOX. This study demonstrates a promising bio-composite for PDT–chemotherapy systematic therapy, which shows potential application in the field of cancer therapy.